Comorbidities of overweight/obesity in Australian preschoolers: cross-sectional population study - Sawyer, M; Hardy, P; Wake, M; Carlin, J (My University, 2008)
OBJECTIVE: To determine relationships between body mass index (BMI) status and indicators of health and morbidity in a nationally-representative population sample of preschool children. METHODS: Data from the 4-5-year-old cohort in the first wave (2004) of the Longitudinal Study of Australian Children were studied. Main outcome measures were: measured child BMI, categorised as non-overweight, overweight and obese using International Obesity TaskForce cutpoints; parent-reported child global health, health-related quality of life, mental health problems, asthma, sleep problems, injuries, special health care needs, and level of parental concern about the child's weight. Regression methods were used to assess associations with child's BMI status, adjusted for sociodemographic factors. RESULTS: BMI was available for 4934 (99%) children; 756 (15.3%) were overweight and 258 (5.2%) obese. Compared to non-overweight children, parents of overweight and obese children reported a higher prevalence of special health care needs (adj OR 1.72, 95% CI 1.20 to 2.46), but other health outcomes were similar. Parental concern about the child's weight was low among the overweight (14.4%) and non-overweight (17.8%) children, but rose to 52.7% in the obese. However, parental concern was unrelated to any of the specific health problems studied. CONCLUSIONS: Despite a high prevalence of overweight/obesity, parents of overweight and obese children reported relatively few additional health burdens over and above those of the non-overweight preschoolers. These findings may shed light on the disparity between strong public concern and parents' expressed lack of concern about overweight/obesity in their own children around the time of school entry.
Archives of Disease in Childhood
Keywords: Health; Surveys and Survey Methodology -- Questionnaire development; Health -- Obesity; Child Development; Families -- Children; Families; Surveys and Survey Methodology; Families and relationships; Health and wellbeing; Surveys and survey methodology; Child Development; Surveys and Survey Methodology; Health; Obesity; Questionnaire development; Surveys and Survey Methodology